药品纸盒包装机开盒机构运动方案设计与分析 - 曹巨江; 徐光中; 祁宇明 (Jixie chuandong)
A kind of opening-box mechanism in the medicine-packing machine is introduced.Using the mechanism kinematical graph and cycle graph,the mechanism kinematical process has been analyzed.